Tissue Plasminogen Activator Levels and Risk of Breast Cancer in a Case–Cohort Study on Italian Women: Results from the Moli-sani Study - Costanzo, Simona; Parisi, Roberta; De Curtis, Amalia; Gamba, Sara; Russo, Laura; Persichillo, Mariarosaria; Panzera, Teresa; Marchetti, Marina; Cerletti, Chiara; de Gaetano, Giovanni; Falanga, Anna; Donati, Maria Benedetta; Iacoviello, Licia; on behalf of the Moli-sani Investigators (Thrombosis and Haemostasis, 2020)
Background Elevated levels of key enzymes of the fibrinolytic system, such as tissue plasminogen activator (tPA), are reported as predictors of poor outcome in cancer patients. Limited information is available about their potential predictive value for breast cancer (BC) risk in the general population.Aim We examined the association of tPA levels with BC risk in a case–cohort study including women from the prospective Moli-sani cohort.Methods A sample of 710 women (mean age: 54.6 ± 12.1 years) was selected as a subcohort and compared with 84 BC cases, in a median follow-up of 4.2 years. Incident cases of BC were validated through medical records. tPA plasma levels were measured using an enzyme-linked immunosorbent assay kit. Hazard ratio (HR) and 95% confidence interval (CI), adjusted for relevant covariates, were estimated by a Cox regression model using the Prentice method.Results Compared with the lowest quartile (<4.9 ng/mL), women in the highest quartile of tPA (>11.2 ng/mL) had increased risk of BC (HRIVvsI: 2.20, 95% CI: 1.13–4.28) after adjusted for age, smoking, education, menopause, and residence. Further adjustment for biochemical markers did not modify this association. The risk of BC increased by 34% for each increase in 1 standard deviation of log-transformed tPA levels (p = 0.046). Elevated levels of tPA were associated mainly with estrogen-receptor-positive BC (2.08, 95% CI: 1.18–3.66).Conclusion Higher levels of tPA, reported to predict cardiovascular risk, are a potential biomarker for BC risk, supporting the hypothesis of a “common soil” linking the pathogenic mechanisms of hormone-dependent tumors and cardiovascular disease.
Keywords: tissue plasminogen activator; breast cancer; case–cohort study